Pls guys ans my question as fast as possible
Attachments:
![](https://hi-static.z-dn.net/files/daa/cbfaa4c7f835aade8194b5c67550eb96.jpg)
Answers
Answered by
1
Answer:
hey here is your answer
so pls mark it as brainliest
Step-by-step explanation:
now here x-1/x=3
thus squaring both sides
we get
x square+1/x square-2x.1/x=9
ie x square+1/x square-2=9
so x square+1/x square=11
so now then
(x square+1/x square)+(x-1/x)
=11+3
=14
hence your final answer is 14
Similar questions
English,
1 month ago
Computer Science,
1 month ago
Social Sciences,
3 months ago
Math,
11 months ago
English,
11 months ago
Biology,
11 months ago